Persistent Basophilia May Suggest an “Accelerated Phase” in the Evolution of CALR-Positive Primary Myelofibrosis Toward Acute Myeloid Leukemia - Dobrowolski, Jerome; Pasca, Sergiu; Teodorescu, Patric; Selicean, Cristina; Rus, Ioana; Zdrenghea, Mihnea; Bojan, Anca; Trifa, Adrian; Fetica, Bogdan; Petrushev, Bobe; Rosu, Ana-Maria; Berindan-Neagoe, Ioana; et al. (Frontiers in Oncology, 2019)
Basophils are white blood cells that play an important role in the human immune system. These cells physiologically increase in number in immune response to certain allergies, chronic inflammation and parasitic infections. But are also a significant indicator for the presence of certain malignancies such as chronic myeloproliferative neoplasms and acute myeloid leukemia. In the current manuscript we present a statistically significant correlation between increasing basophilia in primary myelofibrosis (PMF) and the risk for the subsequent development of an acute myeloid leukemia. We retrospectively identified in the files of the Department of Hematology, Ion Chiricuta Clinical Cancer Center in Cluj Napoca, Romania 623 consecutive patients diagnosed with AML over a period spanning from 2008 to 2018. We afterwards identified 32 patients with AML diag-nosis following a previous diagnosis of myelofibrosis (either post-PV, post-ET, or post-PMF). All the patients being diagnosed according to the WHO criteria. we subsequently established a control group consisting of 32 patients with underlying BCR-ABL negative MPN, that did not develop an AML (AML negative group). Following this, we tried to identify whether the AML negative patients from our control group also display a persistent (>3 months) absolute basophilia. Comparing both group of patients with myelofibrosis, the one group with subsequent AML development and the group without AML, total follow-up did not present statistically sig-nificant differences between both groups. In the univariate analysis patients who progressed to AML had more frequently basophilia, a higher basophilia duration, a higher pre-therapy absolute and relative basophil count and presented more frequently calreticulin (CALR) mutations. Thus, emphasize the need for a closer clinical monitoring for chronic MPNs with marked basophilia, with deep potential clinical impact.